Nursing Care for the Elderly with Cancer in Palliative Care: Integrative Literature Review - Dayara de Nazaré Rosa de Carvalho; Daiane Baldo Apolinário; Viviane Ferraz Ferreira de Aguiar; Dandara de Fátima Ribeiro Bendelaque; Marcela Raissa Asevedo Dergan; Kelly de Cássia Peixoto de Oliveira Silveira; Fabiana de Souza Orlandi; Simone Aguiar da Silva Figueira; Ivonete Vieira Pereira Peixoto (Archives of Current Research International, 2024)
Objective: To know the scientific evidence in the national literature on nursing care for the elderly with cancer in palliative care from 2011 to 2021. Methodology: Integrative Literature Review (INR) Study, using the following databases: SciELO, VHL and CAPES Periodicals. Articles published in Portuguese, English and Spanish were selected for this study; research available in full and online published between the years 2011 and 2021, in the areas of field research and excluding gray literature publications, editorials, letters to the editor, incomplete articles, reflective studies and studies that did not address the topic relevant to the objective of the study, published before the proposed period or pre-print articles. After this moment, the textual corpus was prepared with the conclusions of the articles selected in the final sample, for processing and analysis in the IRAMuTeQ® software. Results: 10 articles were selected to compose this Integrative Review, from the years 2020, 2018, 2011, 2011 and 2021. With 4 publications located in the CAPES database, 4 in the VHL and 2 in SciELO. The interpretation of the corpus generated the following classes: 1) Humanized care for the elderly with cancer in palliative and family care; 2) The importance of palliative care for the physical, spiritual and emotional well-being of the elderly; 3) Nursing interventions for the elderly in palliative care and terminality process. Conclusion: The nurse’s assistance is indispensable in the execution of palliative care, being the professional responsible for guiding, recording and explaining the oncological process in which their patients are, and offering the improvement and relief of their health condition.